Lion in the White House : a life of Theodore Roosevelt - Donald, Aïda DiPace (Basic Books, 2007)
Reassesses the life and political career of Theodore Roosevelt and examines his accomplishments, including his dedication to environmental preservation, the construction of the Panama Canal, and his receipt of the Nobel Peace Prize.